Current Strategies for Tumor Photodynamic Therapy Combined With Immunotherapy - Hua, Jianfeng; Wu, Pan; Gan, Lu; Zhang, Zhikun; He, Jian; Zhong, Liping; Zhao, Yongxiang; Huang, Yong (Frontiers in Oncology, 2021)
Photodynamic therapy (PDT), as a new minimally invasive tumor treatment method, is becoming popular in current tumor treatment research due to its low invasiveness and weak toxic side effects. In recent years, immunotherapy has also made significant progress in the clinical application of advanced metastatic recurrent tumors. The advantages of PDT combined with immunotherapy over stand-alone therapies include inhibition of metastasis and prevention of tumor recurrence without significant adverse effects. This review will briefly outline the principles, types and tumor-killing mechanisms of action of PDT and the associated immune response mechanisms mediated by PDT. In addition, this review discusses recent advances in PDT in combination with selected immunotherapies including cancer vaccines, immune adjuvants, immunosuppressive agents and immune checkpoint blockade for the treatment of tumors.